Evaluation of the Effect of Education Provided by Pharmacists on Hyperlipidemic Patient’s Adherence to Medications and Blood Level of Lipids - Maryam Mehrpooya, Amir Larki-Harchegani, Davoud Ahmadimoghaddam, Mitra Kalvandi, Younes Mohammadi, Masoumeh Taravati Javad, Sara Ataei (Journal of Applied Pharmaceutical Science, 2018)
Background: Hyperlipidemia is one of the most common chronic diseases. Studies show that many patients have sub¬optimal adherence to statin medication which leads to serious negative health consequences. The aim of this study was the evaluation of the effect of education by pharmacists for hyperlipidemic patients treated with statins on patient’s adherence to medication and their level of blood lipids. Material & Methods: This clinical trial included 50 patients with heart disease treated with statins who referred to the Hamadan Farshchian Hospital from January to June 2016. The study’s data collection tools included a demograph¬ic and Morisky questionnaire and their lipid profile before and 6 month after intervention. Data were analyzed by SPSS/16 using T-test, Mann-Withney and X2 tests. Results: Data analysis reflects the homogeneity of medication adherence and the levels of lipid profile in both groups before the intervention but after intervention the medication adherence increased in the intervention group (p < 0.001) and level of LDL significantly decreased (p = 0.02), however, after the intervention there were no statistical difference in the level of HDL, triglyceride and total cholesterol in both groups. Conclusion: Findings of the study suggest that educational counseling by pharmacists could have a positive role in patient’s adherence to drugs and blood level of LDL.
Keywords: High blood cholesterol levels,Medication Adherence,Lipids.